2018
DOI: 10.1016/j.ebiom.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β3 Promotes MUC5AC Hyper-Expression by Modulating Autophagy Pathway in Airway Epithelium

Abstract: Mucus secretion accumulation in the airways may act as a contributing factor for the development of airflow limitation in severe fetal asthma patients. Accumulated evidences showed that transforming growth factor beta (TGF-β) plays a regulatory role in airway remodeling including mucus hyper-secretion in asthma. However, the detailed molecular mechanisms of TGF-β3 induced MUC5AC hyper-expression in airway epithelium remains unclear. Here, we demonstrated the pivotal roles of autophagy in regulation of MUC5AC h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
2
19
0
1
Order By: Relevance
“…Our data suggested that the inhibition of ROS production by NAC in TGF-β3-activated epithelial cells significantly decreased autophagy flux (Figures 3(a)-3(d)). We previously found that TGF-β3 stimulation in the epithelial cells was associated with an increase in mucus production and autophagy was required for TGF-β3-induced MUC5AC levels in 16HBE cells [24]. In this study, immunofluorescence staining revealed that MUC5AC protein was significantly reduced in 16HBE cells treated with TGF-β3 and NAC compared to 16HBE cells treated with TGF-β3 only (Figures 3(e) and 3(f)).…”
Section: Tgf-β3supporting
confidence: 58%
See 4 more Smart Citations
“…Our data suggested that the inhibition of ROS production by NAC in TGF-β3-activated epithelial cells significantly decreased autophagy flux (Figures 3(a)-3(d)). We previously found that TGF-β3 stimulation in the epithelial cells was associated with an increase in mucus production and autophagy was required for TGF-β3-induced MUC5AC levels in 16HBE cells [24]. In this study, immunofluorescence staining revealed that MUC5AC protein was significantly reduced in 16HBE cells treated with TGF-β3 and NAC compared to 16HBE cells treated with TGF-β3 only (Figures 3(e) and 3(f)).…”
Section: Tgf-β3supporting
confidence: 58%
“…Smad2-siRNA lentivirus vectors and Smad3-siRNA lentivirus vectors were purchased from GeneChem Technology (Shanghai, China). 16HBE cells (2 × 10 5 /ml) were transduced as previously described [24].…”
Section: Cell Culture Transfection and Lentiviral Transductionmentioning
confidence: 99%
See 3 more Smart Citations